2014
DOI: 10.1111/hepr.12282
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality of autophagic function and cathepsin expression in the liver from patients with non‐alcoholic fatty liver disease

Abstract: These results indicate that a decrease in hepatic cathepsin expression in NAFLD is associated with autophagic dysfunction. Hepatic inflammation correlates with autophagic dysfunction in NAFLD. These findings indicate that the suppression of autophagic proteolysis by hepatic steatosis is involved in the pathogenesis of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 37 publications
4
92
0
1
Order By: Relevance
“…Several mechanisms may account for this decline in autophagy [112]: (1) increased degradation of autophagy-related gene-7 by an obesity-induced calcium-dependent protease calpain-2 [111]; (2) hyperactivation of the mammalian/mechanistic target of rapamycin signaling, a major autophagy inhibitory pathway, by increased amino acid flux into hepatocytes following overnutrition [113]; and (3) a defect in lysosomal acidification and reduction in cathepsin L that impairs substrate degradation in autolysosomes [114]. Cathepsin B, D, and L expression levels are significantly decreased in the liver of NAFLD patients [115]. Obesity-associated alterations in other signaling pathways may also regulate autophagy to influence NAFLD development and progression, particularly pathways involved in energy sensing of cells, such as AMPK and PI3K.…”
Section: Autophagy and Fatty Livermentioning
confidence: 99%
“…Several mechanisms may account for this decline in autophagy [112]: (1) increased degradation of autophagy-related gene-7 by an obesity-induced calcium-dependent protease calpain-2 [111]; (2) hyperactivation of the mammalian/mechanistic target of rapamycin signaling, a major autophagy inhibitory pathway, by increased amino acid flux into hepatocytes following overnutrition [113]; and (3) a defect in lysosomal acidification and reduction in cathepsin L that impairs substrate degradation in autolysosomes [114]. Cathepsin B, D, and L expression levels are significantly decreased in the liver of NAFLD patients [115]. Obesity-associated alterations in other signaling pathways may also regulate autophagy to influence NAFLD development and progression, particularly pathways involved in energy sensing of cells, such as AMPK and PI3K.…”
Section: Autophagy and Fatty Livermentioning
confidence: 99%
“…Indeed, we have also reported that the number of autophagic vesicles in hepatocytes was increased in NAFLD patients 19) . Additionally, our collaborators have demonstrated that liver-specific autophagydeficient mice harbor adenomas linked to both the formation of p62-and Keap1-positive cellular aggregates and induction of Nrf2 targets (Figure-8).…”
Section: Autophagy Dysregulation In Pathogenesis Of Nashmentioning
confidence: 78%
“…However, some authors did not observe an atenuated fusion capacity. Instead, they report a decrease in clearance of autophagosomes due to a disturbed acidiication of lysosomal compartments [96,97] and/or downregulated cathepsin expression [71,96].…”
Section: Contextual Variability Of Autophagy In Lipid Metabolismmentioning
confidence: 99%
“…Nonetheless, a small post-mortem study demonstrated decreased LC3 and increased p6 staining in relation with the degree of steatosis, suggesting decreased autophagy in more severe steatosis [37]. Likewise, in proven N"FLD p6 accumulation, increased numbers of autophagic vesicles were demonstrated [71]. mRN" and protein analysis of liver biopsies were also indicative of an impaired autophagic lux in both N"FL and N"SH patients [7 ]. "…”
Section: Autophagy As a Lipolytic Mechanismmentioning
confidence: 99%